Social support for child abuse cases in institutional care - Abd Manaf, Abdul Razak; Mokhtar, Norliza (2013)
The purpose of the study is to initially examine the experience and interpretation of support received by the sexual abuse victims living in institutional care.Five teenage female participants were interviewed.Preliminary results of this qualitative study revealed a number of critical issues that may be considered seriously by the stakeholders.One of the concerns is the on-going traumatic experiences faced by the victims.Dealing with several psychosocial challenges, participants are more likely to share their problems and get support from their peers that are close to them in comparison to the staffs in the institution.The findings of this study suggested a number of social work implications that must be addressed regarding the welfare and well-being of sexual abuse victims.